Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 117910 by bemath last updated on 14/Oct/20

∫ sin^(−1) ((√x)) dx =?

sin1(x)dx=?

Commented by bemath last updated on 14/Oct/20

Answered by Lordose last updated on 14/Oct/20

  ∫ sin^(−1) ((√x)) dx =?  u=(√x)⇒dx=2udu  2∫usin^(−1) (u)du  IBP  2((u^2 /2)sin^(−1) (u) − (1/2)∫(u^2 /( (√(1−u^2 ))))du)  u^2 sin^(−1) (u) − ∫ ((sin^2 θcosθdθ)/(cosθ)) {u=sinθ}  u^2 sin^(−1) (u) − ∫sin^2 θdθ  u^2 sin^(−1) (u) − ((θ/2) − ((sinθcosθ)/2)) + C  u^2 sin^(−1) (u) − ((sin^(−1) (u))/2) + ((u(√(1−u^2 )))/2) + C  (1/2)sin^(−1) ((√x))(2x−1) + ((√(x−x^2 ))/2) + C

sin1(x)dx=?u=xdx=2udu2usin1(u)duIBP2(u22sin1(u)12u21u2du)u2sin1(u)sin2θcosθdθcosθ{u=sinθ}u2sin1(u)sin2θdθu2sin1(u)(θ2sinθcosθ2)+Cu2sin1(u)sin1(u)2+u1u22+C12sin1(x)(2x1)+xx22+C

Answered by Dwaipayan Shikari last updated on 14/Oct/20

∫2usin^(−1) u du        x=u^2 ⇒1=2u(du/dx)  =u^2 sin^(−1) u−∫(u^2 /( (√(1−u^2 ))))du  =u^2 sin^(−1) u+∫(√(1−u^2 ))−(1/( (√(1−u^2 ))))du  =u^2 sin^(−1) u+∫cosθ(√(1−sin^2 θ))dθ−sin^(−1) u         u=sinθ  =(x−1)sin^(−1) ((√x))+(1/2)θ+(1/2)∫cos2θdθ  =(x−1)sin^(−1) ((√x))+(1/2)sin^(−1) ((√x))+(1/4)sin(2sin^(−1) (√x))+C  =(1/2)(2x−1)sin^(−1) ((√x))+(1/4)sin(2sin^(−1) (√x))+C  ★sin(2θ)=2sinθcosθ=2(√x)(√(1−x))=2(√(x−x^2 ))

2usin1udux=u21=2ududx=u2sin1uu21u2du=u2sin1u+1u211u2du=u2sin1u+cosθ1sin2θdθsin1uu=sinθ=(x1)sin1(x)+12θ+12cos2θdθ=(x1)sin1(x)+12sin1(x)+14sin(2sin1x)+C=12(2x1)sin1(x)+14sin(2sin1x)+Csin(2θ)=2sinθcosθ=2x1x=2xx2

Answered by 1549442205PVT last updated on 14/Oct/20

Find F=∫ sin^(−1) ((√x)) dx =  Put (√x)=t⇒dt=(dx/(2(√x))).⇒dx=2tdt  F=∫ sin^(−1) ((√x)) dx =∫2tsin^(−1) (t)dt  =∫sin^(−1) (t)d(t^2 )= _(by part) t^2 sin^(−1) (t)−∫(t^2 /( (√(1−t^2 ))))dt  =t^2 sin^(−1) (t)+∫((1−t^2 )/( (√(1−t^2 ))))dt−∫(dt/( (√(1−t^2 ))))  =t^2 sin^(−1) (t)−sin^(−1) (t)+∫(√(1−t^2 ))dt(1)  Put t=sinu⇒dt=cosudu,(√(1−t^2 )) =cosu  ⇒∫(√(1−t^2 )) dt=∫cos^2 udu=(1/2)∫(1+cos2u)du  =(u/2)+(1/4)sin2u=(1/2)sin^(−1) t+(1/2)sinucosu  =(1/2)sin^(−1) (t)+(1/2)t(√(1−t^2 )) (2)  From(1)(2)we get:  F=t^2 sin^(−1) (t)−(1/2)sin^(−1) (t)+(1/2)t(√(1−t^2 ))  =(x−(1/2))sin^(−1) ((√x))+(1/2)(√( x(1−x))) +C

FindF=sin1(x)dx=Putx=tdt=dx2x.dx=2tdtF=sin1(x)dx=2tsin1(t)dtMissing \left or extra \right=t2sin1(t)+1t21t2dtdt1t2=t2sin1(t)sin1(t)+1t2dt(1)Putt=sinudt=cosudu,1t2=cosu1t2dt=cos2udu=12(1+cos2u)du=u2+14sin2u=12sin1t+12sinucosu=12sin1(t)+12t1t2(2)From(1)(2)weget:F=t2sin1(t)12sin1(t)+12t1t2=(x12)sin1(x)+12x(1x)+C

Terms of Service

Privacy Policy

Contact: info@tinkutara.com